Prevalence and genetic characterization of noroviruses in children with acute gastroenteritis in Senegal, 2007–2010. Issue 6 (9th December 2021) - Kebe, Ousmane; Fernandez‐Garcia, Maria‐Dolores; Zinsou, Boris‐Enock; Diop, Amadou; Fall, Amary; Ndiaye, Ndack; Vinjé, Jan; Ndiaye, Kader
Abstract: Norovirus is the leading cause of sporadic and epidemic acute gastroenteritis (AGE) in children and adults around the world. We investigated the molecular diversity of noroviruses in a pediatric population in Senegal between 2007 and 2010 before the rotavirus vaccine implementation. Stool samples were collected from 599 children under 5 years of age consulting for AGE in a hospital in Dakar. Specimens were screened for noroviruses using the Allplex™ GI‐Virus Assay. Positive samples were genotyped after sequencing of conventional reverse transcription‐polymerase chain reaction products. Noroviruses were detected in 79 (13.2%) of the children, with GII.4 (64%) and GII.6 (10%) as the most frequently identified genotypes. Our study describes the distribution of genotypes between 2007 and 2010 and should be a baseline for comparison with more contemporary studies. This could help decision‐makers on possible choices of norovirus vaccines in the event of future introduction.